Pregnancy in Takayasu arteritis - maternal and fetal outcome - Garikapati, Kavitha; Kota, Lakshmi Narayana; Kodey, Prabha Devi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Takayasu arteritis is a rare medical disorder of primary vasculitis of unknown etiology. It affects reproductive age women. It is rare disease and associated with serious maternal and fetal complications and long term morbidity. Methods: Retrospective analysis of patients with diagnosed Takayasu arteritis, to know the impact of disease on maternal status and evaluate fetal outcome. The objective of this study was to know the maternal and fetal outcome in pre-diagnosed cases of Takayasu arteritis. The necessity of accurate measurement of pulse and blood pressures in all the limbs in a suspected case of hypertension in antenatal women at any period of gestation and TYPE the disease accordingly. 3. To evaluate the typing of TA on maternal and fetal outcome. Results: All the 4 patients with TA had medical complication like hypertension in the form of chronic hypertension and pre eclampsia that needed good monitoring of BP in all 4 limbs. Conclusions: As the typing of disease increased, more medical and obstetric complications were noticed.